Research to Produce New Knowledge: The Case in Applied Linguistics RAIs Published in Reputable Journals - Warsidi Warsidi; Firman Firman; Muhammad Affan Ramadhana (Journal of English Language Studies, 2026)
Reviewing earlier literature has suggested that research must produce new knowledge. However, while many linguist scholars have rhetorically analyzed the structures of research article introductions (RAIs), strategic ways and steps to produce new knowledge in RAIs have not been explicitly addressed and explored in the literature. Understanding this need calls this study by addressing three important purposes: providing comprehension of strategic ways, rhetorical steps to produce new knowledge and types of new knowledge in RAs. To execute these purposes, this study used 30 English-applied linguistic RAIs published in reputable journals. The analysis employed a genre analysis approach and used a qualitative method for reporting data analysis results. The results revealed that the authors employed three strategic ways and three rhetorical steps to produce new knowledge. Besides, they produced two types of knowledge: research-world knowledge, and real-world knowledge. These findings suggested that producing new knowledge in research articles requires strategic ways and rhetorical steps, and authors need to emphasize their research contribution to expand knowledge based on earlier research. These findings suggest that English for Academic Purposes (EAP) teachers may take these findings into their academic teaching classes for impactful research.